2015
DOI: 10.1177/0276237415570000
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Art in Museums

Abstract: Research has shown that genuine artworks in the museum are appreciated more than reproductions in the laboratory. However, in previous studies, the effects of genuineness (authenticity or originality) and physical context varied together. Therefore, here we attempted to dissociate the impact of genuineness and physical context on the experience of art by using a 2 Â 2 between-subjects design. Participants (N ¼ 110) were randomly assigned to one of four conditions: gallery/ genuine, gallery/reproduction, labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…When separately manipulating physical contexts (museum vs laboratory) and genuineness (genuine vs reproduction), the museum enhancement effect was not revealed when assessing conceptual artworks related to the medium of photography (Brieber et al 2015a), but was shown in the case of canvas paintings (Grüner et al 2019): figurative and abstract painted art was liked more and rated as more interesting in the museum than in the laboratory. It is likely that Brieber and colleagues (Brieber et al 2015a) did not reveal the effect of the physical context because of the use of photographyan art medium that may not benefit from an Bin person^viewing context. Therefore, the argument can be made that tangible formal aspects must be seen Bin personŝ o that the gallery's context can be revealed (cf.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…When separately manipulating physical contexts (museum vs laboratory) and genuineness (genuine vs reproduction), the museum enhancement effect was not revealed when assessing conceptual artworks related to the medium of photography (Brieber et al 2015a), but was shown in the case of canvas paintings (Grüner et al 2019): figurative and abstract painted art was liked more and rated as more interesting in the museum than in the laboratory. It is likely that Brieber and colleagues (Brieber et al 2015a) did not reveal the effect of the physical context because of the use of photographyan art medium that may not benefit from an Bin person^viewing context. Therefore, the argument can be made that tangible formal aspects must be seen Bin personŝ o that the gallery's context can be revealed (cf.…”
Section: Introductionmentioning
confidence: 91%
“…However, in our study genuine installations were shown in the gallery, while in the classroom participants viewed videos presenting installation artworks. This way of examining the effect of the physical context of the art reception on aesthetic experiences became the subject of criticism of researchers who designed an experiment in which they dissociated the physical context and genuineness factors (Brieber et al 2015a)and did not show the influence of any of these factors. Interpreting the obtained results, these researchers argue in favour of the possibility of the occurrence of an inverse white cube effect, which they explain as follows:…”
Section: The Physical Context and Appreciation Of The Exhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using standardized physiological measures (heart rate, skin conductance, etc.) may be a good strategy to assess the visitor's aesthetic experience in an art museum, as they could help, more than self-reports, to control for the subjective variability linked to individual preferences or cultural differences in the appreciation of museum experiences (Brieber, Leder, & Nadal, 2015;Tschacher et al, 2011). Clow and Fredhoi (2006) aimed to study possible stress reduction of a group of visitors to the Guildhall Art Gallery, London.…”
Section: Art Museums As Restorative Environmentsmentioning
confidence: 99%